Microplastic rapid screening method development using automated mineralogy - Rogers, Gareth H.; Hamdy, Louise B.; McGarry, Amy L.; Gold, David P. (Frontiers in Earth Science, 2022)
Microplastic is a significant global problem. The rapid screening of environmental matter is highly beneficial to the efficient detection, analysis and mapping of microplastic pollution, however many current laboratory techniques to test samples are time-consuming and often involve hazardous chemicals. SEM-based automated mineralogy (AM) is a uniquely powerful tool for quantifying chemical, mineral and textural properties for a wide-range of sample types. This paper presents an attempt to use AM to identify and quantify microplastic within a heterogeneous surrounding matrix using QEMSCAN® (Quantification and Evaluation of Minerals by Scanning Electron Microscopy). Here, the standard AM processes are adapted to develop an entirely new methodology, involving the use of a novel mounting medium for sample preparation and the building of a Species Identification Protocol (SIP) using polymer standards. The results show potential, although challenges include the over-quantification of plastic and differentiation from natural matter. Additional challenges relate to limitations regarding the particular AM system used, which places restrictions on methodology, but which may be overcome with newer systems. This study indicates that, with further refinement, AM may have future potential as a high-throughput, cost-effective, initial screening step to identify highly microplastic-polluted areas and accelerate research into establishing solutions.